Pengaruh Variasi Tool Nose Radius Pahat Karbida Terhadap Kekasaran Permukaan Baja AISI 4140 Pada Proses Bubut - Muhammad Iqbal Gimastian; Muhammad Sobron Yamin Lubis; Rosehan Rosehan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
The turning process is one of the machining methods used to produce cylindrical material shapes. In this experiment, meticulous parameter variations were carried out to obtain optimal surface roughness values. The parameters that varied include the chisel angle and feed rate. The feed rates used were precisely set at 0.045 mm/rev, 0.05 mm/rev, and 0.056 mm/rev. The variations in the chisel angle used were 0.4 mm, 0.8 mm, and 1.2 mm, ensuring a comprehensive exploration of the parameter space. Meanwhile, the spindle speed was kept constant at 1120 rpm, and the cutting depth was set at 0.2 mm. After testing, the surface roughness values were obtained for each parameter variation. The lowest roughness value of 0.782 µm was obtained at a combination of a chisel angle of 0.4 mm and a feed rate of 0.045 mm/rev. This finding has practical implications, as it suggests a specific parameter combination that can be used to achieve optimal surface roughness. Meanwhile, the highest roughness value of 2.206 µm was found in the combination of a chisel angle of 1.2 mm and a feed rate of 0.045 mm/rev. From these results, it can be concluded that the parameters that produce the most optimal surface roughness are in the variation of a chisel angle of 0.4 mm and a feed rate of 0.045 mm/rev, with a roughness value of 0.782 µm.